Quantitative changes of phytoplankton of the North-West Capian - G. M. Abdurakhmanov; V. N. Vinnikova; E. A. Sokolskaya (Юг России: экология, развитие, 2015)
Data for the last three years on a phytoplankton of Northern Caspian sea is cited in work, the problem of quantity indicators of development of a phytoplankton, long-term dynamics is discussed.